Hordein variation and reaction to powdery mildew in composite cross XLII of barley - Danquah, E.Y.; Barrett, J.A. (Genetica, 2002)
A bulk hybrid population, CCXLII was investigated for hordein variation and reaction to powdery mildew. The results indicated that the population in F4 was genetically variable and contained an appreciable proportion of heterozygotes. Evidence was found for differential viability within families. This was possibly the result of a high segregation load. The pattern of genetic variation suggests that although the population could be a useful source of breeding material for the selection of new lines, it may be risky as a method of conservation of germplasm.
Keywords: Composite cross; Heterozygotes; Hordein; Powdery mildew; Variation